Fluorescence Resonance Energy Transfer Characterization of DNA Wrapping in Closed and Open Escherichia coli RNA Polymerase–λP(R) Promoter Complexes - Sreenivasan, Raashi (Biochemistry, 2016)
Initial recognition of promoter DNA by RNA polymerase (RNAP) is proposed to trigger a series of conformational changes beginning with bending and wrapping of the 40–50 bp of DNA immediately upstream of the −35 region. Kinetic studies demonstrated that the presence of upstream DNA facilitates bending and entry of the downstream duplex (to +20) into the active site cleft to form an advanced closed complex (CC), prior to melting of ~13 bp (−11 to +2), including the transcription start site (+1). Atomic force microscopy and footprinting revealed that the stable open complex (OC) is also highly wrapped (−60 to +20). To test the proposed bent-wrapped model of duplex DNA in an advanced RNAP–λP(R) CC and compare wrapping in the CC and OC, we use fluorescence resonance energy transfer (FRET) between cyanine dyes at far-upstream (−100) and downstream (+14) positions of promoter DNA. Similarly large intrinsic FRET efficiencies are observed for the CC (0.30 ± 0.07) and the OC (0.32 ± 0.11) for both probe orientations. Fluorescence enhancements at +14 are observed in the single-dye-labeled CC and OC. These results demonstrate that upstream DNA is extensively wrapped and the start site region is bent into the cleft in the advanced CC, reducing the distance between positions −100 and +14 on promoter DNA from >300 to <100 Å. The proximity of upstream DNA to the downstream cleft in the advanced CC is consistent with the proposed mechanism for facilitation of OC formation by upstream DNA.